A Review of Research on Fault Diagnosis of Gear Transmission Devices Based on Acoustic Signals - Zhang Linhang; Wu Luji; Shi Lubing; Yang Linjie; Qin Jiayin (Jixie chuandong)
As a core component of mechanical equipment, the health status of gear transmission devices is related to various aspects of industrial production. Therefore, the health status monitoring and fault diagnosis of gear transmission devices are of great significance. Firstly, a thorough analysis of the advantages and feasibility of the fault diagnosis based on acoustic signals was conducted, and the process and methods of the fault diagnosis based on acoustic signals were combed. Then, the principle, advantages, limitations and application effect of the acoustic signal denoising, feature extraction and machine learning application methods respectively were expounded and summarized. Finally, the research hotspots and difficulties of the fault diagnosis based on acoustic signals in the field of rotating machinery were pointed out, and prospects for future research directions in the area were made.